TERAPI NOURISH-ART BAGI GANGGUAN KECEMASAN PADA REMAJA KORBAN KEKERASAN FISIK DAN SEKSUAL DI SENTRA HANDAYANI JAKARTA - Nurhayati, Tuti; Rinda Andayani , Rini Hartini; Rustanto , Bambang (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2024)
The issues faced by adolescents who are victims of physical and sexual violence sometimes require social workers to take a long time to understand their condition, as the victims are often not yet willing to open up and are still experiencing anxiety disorders. Nourishment and Art Therapy are among the most frequently applied psychosocial therapies by social workers at Sentra Handayani Jakarta for clients facing these issues. Based on the assessment results of the Nourishment practice applied by social workers, there are still several problems and needs that ultimately require solutions to ensure that Nourishment can be carried out effectively and efficiently. The technological innovation designed is the Nourish-Art Therapy, which is a development of Nourishment and Art Therapy. The purpose of implementing Nourish-Art Therapy is to reduce anxiety levels and enable clients to express their unfinished business issues. The research method applied is the SSD research method using three research subjects. The results of the study, based on analysis and observation of the three research subjects in terms of lack of focus and poor sleep aspects, showed a decrease in anxiety levels in each condition based on the trend direction/graph tendency, data analysis within conditions/situations and between conditions/situations displayed, indicating that the implementation of Nourish-Art Therapy can reduce anxiety levels in adolescents who are victims of physical and sexual violence at Sentra Handayani Jakarta.